Plasma metabolites after 10-weeks of glucose vs fructose-sweetened beverages in subjects with overweight/obesity. - Guirette, Mélanie; Haslam, Danielle E; Ma, Jiantao; Havel, Peter J; Stanhope, Kimber L; Ilkayeva, Olga; Newgard, Christopher B; McKeown, Nicola M; Herman, Mark A (Journal of the Endocrine Society, 2026)
To identify metabolites as potential biomarkers of fructose vs glucose consumption and related metabolic changes, we conducted exploratory metabolomic profiling of fasting blood samples from participants in a double-blind, parallel-arm trial involving 31 male and female adults with overweight or obesity, both before and after supplementation with glucose- or fructose-sweetened beverages. Orthogonal Partial Least Square Discriminatory Analysis (OPLS-DA) was used to identify metabolites that could discriminate between the 2 intervention groups. Changes in 16 metabolites (5 of which are branched-chain amino acid catabolic pathway metabolites) and the branched chain keto acid (BCKA) composite score showed nominal (FDR adjusted P -value <.2, unadjusted P -value ≤.08) differences in response to the 2 interventions. We observed a 2.19 µM (or 13%) and a 10.17 µM (or 25%) increase in ketomethylvaleric acid (P FDR = 0.04, P =.001) and 2-hydroxybutyrate (P FDR = 0.11, P =.008), respectively, after glucose supplementation compared to a null change after fructose supplementation. Notable trends after fructose supplementation included increased long- and median-chain acylcarnitines (ACs); decreased short-chain ACs; and increased homocysteine compared to the glucose supplementation. These data suggest that in people with overweight/obesity, consumption of beverages high in glucose vs fructose may differentially affect the metabolism of branched-chain amino acids and acylcarnitine species reflective of changes in fatty acid oxidation and de novo lipogenesis.